Chercher avec des enfants : la nécessité du désapprentissage - Claire de Saint Martin; Daisy Queiroz (Sociétés et Jeunesses en Difficulté)
The two researches characteristically involve “weak actors” (Payet, Giuliani, Laforgue, 2008), respectively: Brazilian children from a “favela” (shanty town) and French children with special needs, integrating representations of the socially produced categorizations, as well as the educational normativity, such representations hindering their active participations in the research. This paper highlights “the need of unlearning” so that the children can become actors in researches. It is by means of the methodology, regarded as a dynamic process being constructed along the research (Passos, Kastrup, Tedesco, 2014), that this unlearning can be achieved. The ethics issue is important in this process. Encountering differences is essential for destabilizing, and thus collectively creating something new. The ethics issue also consists of a political view (Freire, 2013) in the sense of creating new means of existence and of acting, and, at the same time, other ways of organizing the world. Therefore, several effects of this kind of “research with” the children are to be pointed, not only from the individual perspective, but also from the collective and scientific perspectives.